The effectiveness of Interpersonal Psychotherapy-Adolescent Skills Training for adolescents with depression: a systematic review and meta-analysis - Zheng, Kewei; Xu, Huimin; Qu, Chunhui; Sun, Xianghong; Xu, Na; Sun, Ping (Frontiers in Psychiatry, 2023)
Background : Interpersonal Psychotherapy-Adolescent Skills Training (IPT-AST) is a standardized depression prevention program for adolescents conducted in campus settings. The purpose of this review is to examine the randomized controlled trials of IPT-AST for the prevention of adolescent depression in the past 20 years.Method : A systematic search of relevant electronic databases (PubMed, WOS, Embase, PsycINFO, the Cochrane Library, CNKI and WANFANG DATA) and study reference lists was conducted. Any study investigating the effectiveness of IPT-AST in 12-to 20-year-olds with depressive symptoms was eligible. Synthesis was via narrative summary and meta-analysis.Results :A total of 6 studies met the inclusion criteria. Meta-analysis results showed a remarkable improvement in patients' depressive symptoms after IPT-AST intervention (WMD = -5.05 , 95% CI = -8.11 to -1.98 , p < 0.05, I 2 = 77%). Six month follow-up data showed that the intervention outcomes of IPT-AST remained significant (WMD = -3.09 , 95% CI: -5.23 to -0.94 , p < 0.05, I 2 = 57%).This meta-analysis showed that IPT-AST was effective in adolescents with depressive symptoms at post-prevention and at 6-month follow-up. However, these conclusions are cautious, as they are based on a small number of studies and the presence of author duplication. Future studies should use multi-center, large-sample randomized controlled trials to evaluate the efficacy of IPT-AST for preventing depression in adolescents.